Occult intrasacral meningocoele. Issue 4 (August 1970) - Joseph, Roma A.; McKenzie, Thomas
Abstract : A case is reported of the rare lesion occult intrasacral meningocoele in a 27-year-old woman who developed symptoms for the first time shortly after the birth of her fourth child. The terminology of the condition is discussed and its pathogenesis, mode of presentation, and treatment reviewed.